Oblique wedge extrusion of UHP/HP complexes in the Late Triassic: structural analysis and zircon ages of the Atbashi Complex, South Tianshan, Kyrgyzstan. Issue 10 (27th July 2017) - Sang, Miao; Xiao, Wenjiao; Bakirov, Apas; Orozbaev, Rustam; Sakiev, Kadyrbek; Zhou, Kefa
ABSTRACT: The exhumation and tectonic emplacement of eclogites and blueschists takes place in forearc accretionary complexes by either forearc- or backarc-directed extrusion, but few examples have been well analysed in detail. Here we present an example of oblique wedge extrusion of UHP/HP rocks in the Atbashi accretionary complex of the Kyrgyz South Tianshan. Our field mapping and structural analysis demonstrate that the Atbashi Eclogite–Blueschist Complex is situated in a complicated duplex formed by a northerly dextral transpression system and a southerly sinistral transtension system. The two major shear systems suggest that the Atbashi Complex was extruded obliquely southwestwards during eastward penetration of the southern tip of the Yili–Central Tianshan Arc of the Kazakhstan Orocline during the Late Triassic. Also, we report new zircon U–Pb metamorphic ages of four eclogites and one garnet-bearing quartz-schist from the Atbashi complex of 217–221 Ma and 223.9 Ma, respectively, suggesting that the main extrusion was later than previously proposed and that the final orogenesis was not completed until the Late Triassic. The HP/UHP rocks have an oblique plunge to the NE and extrusion took place southwestwards during escape tectonics along the South Tianshan accretionary wedge in the Late Triassic. Our work shows that the movement of HP/UHP rocks had a 3D style with an arc-parallel structure, and sheds light on earlier 2D models with either forearc- or backarc-directed extrusions, which indicates that more systematic structural and geochronological work is needed to characterize the accretionary tectonics of many orogens around the world. Our data on the timing of extrusion and emplacement of the Atbashi Eclogite–Blueschist Complex also help to resolve the long-standing controversy about the time of terminal orogeny of the Central Asian Orogenic Belt.